Ketiadaan Pengakuan Ecocide Sebagai Core International Crime Dan Implikasinya Terhadap Pertanggungjawaban Pidana Individu - Nola Listi Fitriani; Tiara Intan Camesi; Asep Suherman (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the absence of recognition of ecocide as a core international crime and its implications for individual criminal responsibility under international criminal law. The research employs a normative legal method with statute, conceptual, and comparative approaches. Legal materials are collected through library research and analyzed using qualitative descriptive methods. The results indicate that substantively, ecocide possesses characteristics similar to core international crimes, particularly in terms of its gravity, widespread or systematic impact, and its threat to global interests. However, ecocide has not yet been formally recognized under the Rome Statute 1998 due to the absence of a universally accepted definition and the presence of political and economic challenges. This lack of recognition creates a legal gap, limiting the jurisdiction of the International Criminal Court in prosecuting perpetrators, thereby potentially leading to impunity. Therefore, it is necessary to develop a more adaptive international criminal law framework by recognizing ecocide as an international crime in order to strengthen individual criminal responsibility and enhance global environmental protection.